Discussion on the Mechanism of Collaborative Promotion of Smart Grid Development through Energy Storage and Energy Blockchain - Luan, Jing (International Journal of Electric Power and Energy Studies, 2026)
With a growing share of renewable sources providing most of our electricity generation, they will introduce many unique challenges for tomorrow’s power systems,including important problems of peak load management and scheduling difficulties. Energy storage provides a flexible means to provide energy,plays a key role to solve those problems. Energy blockchain has the characteristics of decentralization, transparency and immutability,provides a new idea for the management of information in energy system, As far as the key problem of how energy storage and energy blockchain could promote the construction of intelligent grid,this work suggests the endogenous relation between energy storage and energy blockchain technology which could be supportive to the evolution of smart grid,and analyses according to its operating mechanism, transaction mode, incentive mechanism and credit mechanism. Soenergy storage and energy block chain can build a grid optimization model combining IoT and data to enhance the flexibility of systems,unleashes the vitality of the distributed power market , fully reflects multi-dimensional values and reduces operation management cost ,and provides novel ideas on how to safely and stably operate smart grids.